(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2026)
Parkinsonian disorders are characterised by dopaminergic depletion and motor dysfunction, prompting growing interest in plant-derived dopamine precursors as supportive therapies. Although Vicia faba L. seeds are known to contain L-DOPA, evidence linking standardised extracts to functional neurobehavioral improvement, together with demonstrated central dopaminergic activity, remains limited. This study aimed to evaluate the neurobehavioral efficacy of a standardised hydro-alcoholic V. faba seed extract and assess its dopaminergic contribution in a haloperidol-induced Parkinsonian rat model. Extract-treated animals showed progressive improvements in paw withdrawal latency, locomotor activity, and exploratory behaviour across treatment levels compared with disease controls, with paw withdrawal time showing strong statistical significance (p <0.001) and locomotor parameters also demonstrating statistically significant improvement across treatment groups. Chromatographic profiling indicated dopaminergic constituents, while brain tissue chromatographic profiles suggested the presence of centrally available levodopa-like constituents following treatment. By integrating behavioural findings with phytochemical and neurochemical evidence, this study supports the functional dopaminergic activity of V. faba extract beyond simple confirmation of its L-DOPA content and highlights its potential as a plant-derived adjunct for Parkinsonian symptom management. Further studies are needed to identify active constituents, clarify pharmacokinetics, and evaluate translational therapeutic relevance.